Efficacy of a Dengue Vaccine Candidate (TAK-003) in Healthy Children and Adolescents 2 Years after Vaccination. (15th December 2020) - López-Medina, Eduardo; Biswal, Shibadas; Saez-Llorens, Xavier; Borja-Tabora, Charissa; Bravo, Lulu; Sirivichayakul, Chukiat; Vargas, Luis Martinez; Alera, Maria Theresa; Velásquez, Hector; Reynales, Humberto; Rivera, Luis; Watanaveeradej, Veerachai; et al.
Abstract: Background: Takeda's dengue vaccine is under evaluation in an ongoing phase 3 efficacy study; we present a 2-year update. Methods: Children (20 099, 4–16 years old) were randomized to receive 2 doses of TAK-003 or placebo 3 months apart and are under surveillance to detect dengue by serotype-specific RT-PCR. Results: Cumulative efficacy against dengue approximately 27 months since first dose was 72.7% (95% confidence interval [CI], 67.1%–77.3%), including 67.0% (95% CI, 53.6%–76.5%) in dengue-naive and 89.2% (95% CI, 82.4%–93.3%) against hospitalized dengue. In the second year, decline in efficacy was observed (56.2%; 95% CI, 42.3%–66.8%) with the largest decline in 4–5 year olds (24.5%; 95% CI, −34.2% to 57.5%); efficacy was 60.6% (95% CI, 43.8%–72.4%) in 6–11 year and 71.2% (95% CI, 41.0%–85.9%) in 12–16 year age groups. As TAK-003 efficacy varies by serotype, changes in serotype dominance partially contributed to efficacy differences in year-by-year analysis. No related serious adverse events occurred during the second year. Conclusions: TAK-003 demonstrated continued benefit independent of baseline serostatus in reducing dengue with some decline in efficacy during the second year. Three-year data will be important to see if efficacy stabilizes or declines further. Clinical Trials Registration. NCT02747927. Takeda's tetravalent dengue vaccine (TAK-003) continued to demonstrate benefit in reducing dengue independent of baseline serostatus up to 2 years after completing vaccination with some decline in efficacy during the second year in 4–16 year olds in dengue-endemic countries.